HUBUNGAN BERAT BADAN LAHIR DENGAN KEJADIAN RUPTURE PERINEUM PADA PRIMIPARA DI BIDAN PRAKTEK MANDIRI LIDYA DI DELITUA TAHUN 2022 - Lidya Vidi Nova Hutajulu; Ninsah Mandala Putri Br Sembiring (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
The process of pregnancy and childbirth is a natural process that occurs in a mother. Perineal Rupture is tearing or tearing of tissue by force. This study aims to determine the relationship between birth weight and the incidence of perineal rupture in Primipara at Independent Practice Midwife Lidya in Delitua in 2022. This type of research is an analytical survey with a cross sectional method approach. The number of samples used was 22 people. The data analysis technique uses the Chi Square test. the results obtained from 22 respondents, obtained a value of p = 0.001 (P> 0.05) this means that there is a relationship between birth weight and the incidence of perineal rupture in Primipara.